Performance of Petroleum Car Engines Around The Railway - Ah Sulhan Fauzi; Kuni Nadliroh (Procedia of Engineering and Life Science, 2021)
The car accident while passing on the railroad tracks is not new anymore. Several assumptions emerged about the cause of the breakdown of the car. Some say it's because of the magnetic field that arises from the friction between railroad iron and railroad wheels. Various internet sites have discussed the problem of car accidents that often occur at train crossings, but do not include the cause of the accident. Logically, it is true that the friction between two metals will cause something that according to physics is called thermal energy in the form of heat. The heat generated by the friction of the railroad tracks and wheels is certainly not the cause of these accidents. In several previous studies, it was stated that the friction between the wheels and railroad tracks causes changes in the earth's magnetic field. The change in the earth's magnetic field is not yet known whether it affects the performance of a car engine. This research will look for the effect of changes in the earth's magnetic field on the performance of car engines. The engine performance under study is to compare car engine speed between car engine speed data due to changes in the earth's magnetic field with car engine speed data without the influence of changes in the earth's field using the t test method for two paired samples. The results of the data test show that changes in the earth's magnetic field do not affect the performance of a car engine speed.